Respostas

2013-05-13T15:16:39-03:00

Você tem apenas que substituir o valor na equação:

 

a) f(-2) = 12 . (-2) - 5 = -24 - 5 = -29

 

b) f(2) = 12 . 2 - 5 = 24 - 5 = 19

 

c) f(0) = 12 . 0 - 5 = 0 - 5 =-5

 

d) f(-1) = 12 . (-1) - 5 = -12 - 5 = -17

 

=D

2013-05-13T15:24:05-03:00

Dada a função f(x) = 12x – 5, obtenha.

a) f(–2) = 12(-2)-5

    f(–2) = 12(-2)-5

    f(–2) = -24-5=-29

 

b) f(+2) =  12(2) – 5

    f(+2) =  24 – 5

   f(+2) =  19

   

 

 

c) f(0) =  12*0 –

    f(0) =  0 –

     f(0) = 

 

d) f(–1) = 12(-1) – 5

     f(–1) = 12(-1) – 5 

     f(–1) = -12 – 5

    f(-1)=-17

 

Espero ter ajudado.

thiau.